An Exact and Efficient Implementation of Threshold Gates with Arbitrary Real Weights - Frandsen, Gudmund Skovbjerg; Sturtivant, Carl (DAIMI Report Series, 1988)
We show how to exactly implement an n input threshold gate with arbitrary real weights by a circuit of constant depth and size polynomial in n. Our circuits use and, or and majority gates as well as unary negation gates. The use of majority is imperative due to certain lower bound results.